Information and Communication Technology Second IFIP TC5/8 International Conference, ICT-EurAsia 2014, Bali, Indonesia, April 14-17, 2014. Proceedings - Linawati; Mahendra, Made Sudiana; Neuhold, Erich J.; Tjoa, A Min.; You, Ilsun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the Second IFIP TC 5/8 International Conference on Information and Communication Technology, ICT-Eur Asia 2014, with the collocation of Asia ARES 2014 as a special track on Availability, Reliability and Security, held in Bali, Indonesia, in April 2014. The 70 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers have been organized in the following topical sections: applied modeling and simulation; mobile computing; advanced urban-scale ICT applications; semantic web and knowledge management; cloud computing; image processing; software engineering; collaboration technologies and systems; e-learning; data warehousing and data mining; e-government and e-health; biometric and bioinformatics systems; network security; dependable systems and applications; privacy and trust management; cryptography; multimedia security and dependable systems and applications.
Applied modeling and simulation -- Mobile computing -- Advanced urban-scale ICT applications -- Semantic web and knowledge management -- Cloud computing -- Image processing -- Software engineering -- Collaboration technologies and systems -- E-learning -- Data warehousing and data mining -- E-government and e-health -- Biometric and bioinformatics systems -- Network security -- Dependable systems and applications -- Privacy and trust management -- Cryptography -- Multimedia security -- Dependable systems and applications.
Keywords: Computer science; Computer communication systems; Computer security; Data structures (Computer science).; Information storage and retrieval; Computers and civilization; Computer Science; Computers and Society; Systems and Data Security; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Structures, Cryptology and Information Theory; Computer Communication Networks; Electronic books